Distribution and Habitat Preferences of Indo-Pacific Bottlenose Dolphins (Tursiops aduncus) Inhabiting Coastal Waters With Mixed Levels of Protection - Haughey, Rebecca; Hunt, Timothy N.; Hanf, Daniella; Passadore, Cecilia; Baring, Ryan; Parra, Guido J. (Frontiers in Marine Science, 2021)
Assessments of species distributions are crucial for informing conservation and management action. In this study, we used ensemble modelling to explain the distribution of Near Threatened Indo-Pacific (IP) bottlenose dolphins (Tursiops aduncus) in coastal waters at the North West Cape (NWC), Western Australia (WA), an area encompassing a marine protected area and adjacent unprotected coastal waters. Analyses used boat-based data collected from 2013 to 2015 and 2018 to 2019. Overall, the distribution of IP bottlenose dolphins was best explained by distance to coast (up to 2000 m) and distance to boat ramp (up to 7000 m). Areas of high probability of occurrence for dolphins extended from the tip and down the eastern side of the NWC and overlapped with designated sanctuary zones as well as waters beyond the boundaries of the Ningaloo Marine Park (NMP). Distribution and habitat preferences varied slightly with season. In autumn, dolphin distribution was best explained by distance to coast and water depth with a higher likelihood of observing dolphins 1000 to 2000 m from the coast and in water depths of 7-10 m deep. During winter months, distance to coast (1000 to 2000 m) and sea surface temperature (21.5°C to 23.5°C) were the most important explanatory variables, with presence in coastal lagoons to the west of the NWC more likely than other seasons. During spring, areas of moderate to high probability of dolphin occurrence were mainly located outside the NMP, with marine park zone (outside the NMP and Sanctuary zones within the NMP, the two zones with the highest probability of IP bottlenose dolphin occurrence) and water depth (waters 7 – 13 m deep) best explaining dolphin distribution. This study highlights the importance of inshore areas of the NWC for IP bottlenose dolphins and the potential vulnerability of this species to increasing and cumulative anthropogenic stressors associated with these areas. Results of this study should be considered in future zoning reviews and adaptive management efforts of the NMP allowing for effective management of this Near Threatened species.